Covid-19 and freedom of movement: A case study of the Malaysian federal constitution - Masum, Ahmad; Ahmad, Muhammad Hassan; Nafees, Seeni Mohamed (The Malaysian Current Law Journal Sdn Bhd, 2021)
Right to freedom of movement underlines the idea that citizens should be allowed to move freely from one place to another. In a sense it also underlines the idea of the country as one unit. Freedom of movement constitutes an important aspect of a citizen's liberty and has always been in the Malaysian scheme of values. Art icle 9(2) of the Malaysian Federal Constitution gives citizens the right to move freely throughout the Federation. Despite the constitutional protection of freedom of movement, this right is not absolute but rather qualified with several restrictions. The various restrictions imposed on freedom of movement include the laws relating to security, public order, public health or punishment of offenders; and such laws cannot be challenged on the ground that it does not relate to any of these matters. Covid-19 policies like the Movement Control Order (MCO) in Malaysia has severely restricted free movement. The paper aims to examine the operation of freedom of movement as a fundamental right under the Malaysian Federal Constitution amidst the outbreak of the Covid-19 pandemic. The paper concludes that under the Malaysian Federal Constitution, freedom of movement is not an absolute right. Restrictions can be imposed on freedom of movement. Therefore, the imposition of the MCO due to the Covid-19 outbreak and the King’s declaration of a nationwide state of emergency to curb the spread of Covid-19 are constitutionally legal. However, the paper recommends that the restrictions imposed should conform to the standards laid down by the Universal Declaration of Human Rights 1948 (UDHR) and the International Covenant on Civil and Political Rights 1966 (ICCPR) which embody the ideas and aspirations of all civilised peoples.